2021
DOI: 10.7150/ijbs.61790
|View full text |Cite
|
Sign up to set email alerts
|

BCAR1 plays critical roles in the formation and immunoevasion of invasive circulating tumor cells in lung adenocarcinoma

Abstract: Background:We investigated the roles of breast cancer anti-estrogen resistance 1 (BCAR1/p130Cas) in the formation and immunoevasion of invasive circulating tumor cells (CTCs) in lung adenocarcinoma (LUAD). Methods: Biomarkers of CTCs including BCAR1 and CD274, were evaluated by the CanPatrol method. Proteomics analysis of LUAD cells and exosomes after BCAR1 overexpression (BCAR1-OE) was performed by mass spectrometry. Cell functions and relevant signaling pathways were investigated after BCAR1 knockdown (BCAR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…BCAR1 has been identified as a new promising biomarker for lung cancer [ 32 ]. Moreover, upregulated BCAR1 predicted poor prognosis in lung cancer patients and was associated with lymph node and distant metastasis and chemotherapy resistance in lung cancer [ 19 , 20 , 33 , 34 ]. In order to explore the specific mechanism of the proliferation and metastatic promotion of ASF1B in LUAD, we first carried out a correlation analysis of ASF1B and BCAR family genes, showing that ASF1B was positively correlated with most of the BCAR family genes at the mRNA level and especially with BCAR1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCAR1 has been identified as a new promising biomarker for lung cancer [ 32 ]. Moreover, upregulated BCAR1 predicted poor prognosis in lung cancer patients and was associated with lymph node and distant metastasis and chemotherapy resistance in lung cancer [ 19 , 20 , 33 , 34 ]. In order to explore the specific mechanism of the proliferation and metastatic promotion of ASF1B in LUAD, we first carried out a correlation analysis of ASF1B and BCAR family genes, showing that ASF1B was positively correlated with most of the BCAR family genes at the mRNA level and especially with BCAR1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the knockdown of ASF1B was accompanied by the decreased expression of BCAR1. Interestingly, BCAR1 has been widely reported to regulate the cell cycle and EMT in cancer [ 16 , 20 , 34 ]. Our current data indicated that ASF1B might promote cell proliferation and migration of LUAD by regulating cell cycle and EMT both.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 4, 6-diamidino-2-phenylindole (DAPI) was used to stain the cells’ nuclei ( 23 , 25 ). The primer sequences used by the probes are detailed in Supplementary Table S2 ( 26 ) ( Figure 1A ; Supplementary Figure S9 ).…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies are being conducted on the progression of exosomes as novel mediators of intercellular communication in multiple types of cancers, including lung carcinogenesis and the tumor microenvironment (TME). Thus, exosomes are known for mediating intercellular communication during tumor development (11)(12)(13)(14). The current review provides an overview of the role of exosomes in NSCLC growth, metastasis, and immune response.…”
Section: Introductionmentioning
confidence: 99%